2019
DOI: 10.5194/acp-19-9949-2019
|View full text |Cite
|
Sign up to set email alerts
|

The remote sensing of radiative forcing by light-absorbing particles (LAPs) in seasonal snow over northeastern China

Abstract: Light-absorbing particles (LAPs) deposited on snow can decrease snow albedo and affect climate through snow-albedo radiative forcing. In this study, we use MODIS observations combined with a snow-albedo model (SNICAR -Snow, Ice, and Aerosol Radiative) and a radiative transfer model (SBDART -Santa Barbara DISORT Atmospheric Radiative Transfer) to retrieve the instantaneous spectrally integrated radiative forcing at the surface by LAPs in snow (RF LAPs MODIS ) under clear-sky conditions at the time of MODIS Aqua… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 81 publications
(143 reference statements)
2
22
0
Order By: Relevance
“…In NA, Qian et al (2009) provided an estimate of 3-7 W m −2 for the central Rockies and southern Alberta in March, while Oaida et al (2015) reported an average RFLS of 16 W m −2 over the western US in spring. Finally, Qian et al (2014) and Qi et al (2017) estimated RFLS values of < 0.3 and 0.024-0.39 W m −2 for the Arctic in April, respectively. We consider our retrievals for NEC to be comparable with these regional model simulations, despite some disparity.…”
Section: Discussionmentioning
confidence: 96%
“…In NA, Qian et al (2009) provided an estimate of 3-7 W m −2 for the central Rockies and southern Alberta in March, while Oaida et al (2015) reported an average RFLS of 16 W m −2 over the western US in spring. Finally, Qian et al (2014) and Qi et al (2017) estimated RFLS values of < 0.3 and 0.024-0.39 W m −2 for the Arctic in April, respectively. We consider our retrievals for NEC to be comparable with these regional model simulations, despite some disparity.…”
Section: Discussionmentioning
confidence: 96%
“…Previous observations have revealed that lightabsorbing particles (LAPs; e.g., black carbon (BC), organic carbon (OC), and mineral dust) within snow may reduce snow albedo and enhance the absorption of solar radiation (Hadley and Kirchstetter, 2012). As a result, LAPs play a major role in the alteration of snow morphology and snowmelt processes and therefore yield important effects on local hydrological cycles and global climate (Qian et al, 2009). Given the importance of the climate feedback caused by LAPs in snow, studies have developed snow radiative models and sought to improve our understanding of the influence of LAP-contaminated snow on climate.…”
Section: Introductionmentioning
confidence: 99%
“…High-resolution mass spectrometry (HRMS) interfaced with soft electrospray ionization (ESI) can help to decipher the complexity of WSOC, providing an explicit description of its individual molecular components (Qi et al, 2020). Thousands of individual organic species with unambiguously identified elemental compositions can be detected at once by ESI-HRMS due to its high mass resolving power, mass accuracy, and dynamic range (Nizkorodov et al, 2011;Noziere et al, 2015).…”
mentioning
confidence: 99%